Analysis The Economy Empowerment based on Ecoprotection in Pondok Modern Darussalam Gontor Putri 6 Poso - Kaltsum, Ummu; Hasan, Asyari; Binarni, Indah (Devotion : Journal of Research and Community Service, 2023)
This study analyzes ecoprotection based economic empowerment in Modern Boarding School Darussalam Gontor for Girl 6 Poso. The aim of this study are to know the economy implementation based on ecoprotection and the involution of boarding scholl in its empowerment. The method was used is field research which is descriptive qualitative by using phenomenological and sociological approach. The results of the study sow that the economy empowerment based on ecoprotection of Gontor Putri 6 was realized by creating business es, the protection system refers on internal environment protection of boarding school from the external environment influence, the involution of Gontor Putri 6 Poso in Economy empowerment based on ecoprotection by the caretaker involutation, the students nurture involutation, admistration staff, and ecsejutive staff refer to the boarding scholl policy. The economy protection system applied bring business es increase in quality and quantity, but this system also had weaknesses and poses a threat, that case was overcome by every business would improve the potential of opportunity.